2008
DOI: 10.4049/jimmunol.181.5.3099
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced CXCL16 Release by Breast Cancer Cells Attracts Effector T Cells

Abstract: Recruitment of effector T cells to inflamed peripheral tissues is regulated by chemokines and their receptors, but the factors regulating recruitment to tumors remain largely undefined. Ionizing radiation (IR) therapy is a common treatment modality for breast and other cancers. Used as a cytocidal agent for proliferating cancer cells, IR in combination with immunotherapy has been shown to promote immune-mediated tumor destruction in preclinical studies. In this study we demonstrate that IR markedly enhanced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
492
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 628 publications
(528 citation statements)
references
References 54 publications
(65 reference statements)
20
492
0
4
Order By: Relevance
“…38 Of interest, CCL2 and CXCL16 induced by CLL exosomes are important chemoattractants for macrophages and T cells, respectively. 63,64 CAF-derived factors are known to modulate immune cell functions, skewing T cells and myeloid cells into immunosuppressive and tumor-promoting Th2/M2-like phenotypes. CCL2, CXCL1, and hepatocyte growth factor (HGF) were found to be elevated in serum of CLL patients vs healthy donors (M. Seiffert, unpublished data, 2014), indicating high clinical relevance.…”
Section: Cll Exosomes Induce Caf Formation 1113mentioning
confidence: 99%
“…38 Of interest, CCL2 and CXCL16 induced by CLL exosomes are important chemoattractants for macrophages and T cells, respectively. 63,64 CAF-derived factors are known to modulate immune cell functions, skewing T cells and myeloid cells into immunosuppressive and tumor-promoting Th2/M2-like phenotypes. CCL2, CXCL1, and hepatocyte growth factor (HGF) were found to be elevated in serum of CLL patients vs healthy donors (M. Seiffert, unpublished data, 2014), indicating high clinical relevance.…”
Section: Cll Exosomes Induce Caf Formation 1113mentioning
confidence: 99%
“…In human glioma, colorectal, breast and renal cancer, tumors with high CXCL16 expression had slower progression and showed infiltration of CD4 and CD8 lymphocytes [53][54][55][56][57]. On the contrary in prostate cancer CXCL16 expression has been correlated with poor prognosis [58].…”
Section: Chemokine Regulation Of Leukocyte Attraction Within Tumorsmentioning
confidence: 99%
“…On the contrary in prostate cancer CXCL16 expression has been correlated with poor prognosis [58]. Interestingly, it has been reported that ionizing radiation therapy markedly enhanced CXCL16 secretion by mouse and human breast cancer cells, which recruited CXCR6+ effector cells [55].…”
Section: Chemokine Regulation Of Leukocyte Attraction Within Tumorsmentioning
confidence: 99%
“…Matsumura et al reported that radiotherapy improved the therapeutic efficacy of immunotherapy, by converting tumors into inflamed tissues (39,40). After exposure to ionizing radiation, enhanced production of pro-inflammatory chemokine CXCL16 was observed in 4T1 breast tumor cells, resulting in reduced tumor growth, in vitro and in vivo, by facilitating the effector phase of the antitumor immune response (39,40). In addition, Horton et al also demonstrated that Trastuzumab (Herceptin) enhanced the effectiveness of radiotherapy, by increasing radio-sensitivity, in breast cancer patients (36).…”
Section: Discussionmentioning
confidence: 99%